Oricymba xianjuensis sp. nov., a new freshwater diatom (Bacillariophyceae) from Xianju National Park (Zhejiang Province, China) - Zhang, Wei; Qi, Xin; Kociolek, J. Patrick; Wang, Li-Qing; Zhang, Rui-Lei (Phytotaxa, 2016)
During a survey of freshwater diatoms from streams in the Xianju National Park, Zhejiang Province, China, a new cymbelloid species, Oricymba xianjuensis sp. nov. has been recorded. This species is assigned to the genus Oricymba by virtue of having a ridge separating the valve face and mantle, the presence of apical pore fields, and areolar openings with dentate occlusions. A detailed morphological description of the new species O. xianjuensis is presented, based on light and scanning electron microscopy. Oricymba xianjuensis sp. nov. is characterized by having a ridge along the valve face, as well as a linear-lanceolate outline with a moderately gibbous central portion gradually tapering towards the round, slightly protracted poles, a slightly lateral raphe with widened proximal endings and strongly deflected distal endings, and radiate striae. The taxon is morphologically compared with similar species of the genus Oricymba. The new species looks most similar to O. latirotundata, but is separated from this species by having more narrow, linear valves and a more tumid ventral margin. These findings add to our understanding the morphology and distribution of the genus Oricymba in China.